PENGAWASAN KEPADA ORGANISASI KEMASYARAKATAN OLEH BADAN KESATUAN BANGSA DAN POLITIK KOTA SEMARANG TAHUN 2022 (SESUAI PERMENDAGRI NOMOR 56 TAHUN 2017) - Sabila Fitra Pertiwi; Nunik Retno Herawati; Dewi - Erowati (Journal of Politic and Government Studies, 2023)
One of the most important elements in a democratic country is the realization of the freedom to associate and assemble, as demonstrated through civil society representation in organizations outside the government, namely civil society organizations. The freedom for people to be part of an organization and carry out its activities freely becomes a fundamental right that must be protected by the state. However, since the enactment of Regulation of the Ministry of Home Affairs Number 56 of 2017, the National Unity and Politics Agency as a part of the government is obligated to provide guidance and supervision of civil society organizations at the regional level. This policy has sparked both pros and cons as it is seen as a setback for democracy. The purpose of this research is to understand the phenomenon of the presence of civil society organizations (CSOs) in Semarang City, why these CSOs need to be monitored, and how the supervision of CSOs by the National Unity and Politics Agency of Semarang City is conducted, examined through five types of supervision methods: direct supervision, indirect supervision, formal supervision, informal supervision, and administrative supervision. The research method used in this study is qualitative descriptive method with data collection techniques through indepth interviews and literature review. The research results show that the CSOs in Semarang City have been carrying out their work and activities well and in accordance with the applicable regulations. However, supervision must still be conducted as a preventive and punitive measure to maintain the peace and order of Semarang City from issues or deviations that CSOs may engage in. The supervision of CSOs by the National Unity and Politics Agency of Semarang City, based on Regulation of the Ministry of Home Affairs Number 56 of 2017, has been technically well-executed and does not restrict the existence of CSOs as long as their institutions and activities do not violate the laws and regulations. Nevertheless, there are still challenges related to a lack of human resources in implementing this supervision. Therefore, improvements in the operational supervision are needed to make the supervision of CSOs in Semarang City more effective and efficient